Effect of the implosion and demolition of a hospital building on the concentration of fungi in the air. Issue 12 (8th October 2015) - Barreiros, Gloria; Akiti, Tiyomi; Magalhães, Ana Cristina Gouveia; Nouér, Simone A.; Nucci, Marcio
Summary: Building renovations increase the concentration of Aspergillus conidia in the air. In 2010, one wing of the hospital building was imploded due to structural problems. To evaluate the impact of building implosion on the concentration of fungi in the air, the demolition was performed in two phases: mechanical demolition of 30 m of the building, followed by implosion of the wing. Patients at high risk for aspergillosis were placed in protected wards. Air sampling was performed during mechanical demolition, on the day of implosion and after implosion. Total and specific fungal concentrations were compared in the different areas and periods of sampling, using theanova test. The incidence of IA in the year before and after implosion was calculated. The mean concentration of Aspergillus increased during mechanical demolition and on the day of implosion. However, in the most protected areas, there was no significant difference in the concentration of fungi. The incidence of invasive aspergillosis (cases per 1000 admissions) was 0.9 in the 12 months before, 0.4 during, and 0.5 in the 12 months after mechanical demolition ( P > 0.05). Continuous monitoring of the quality of air and effective infection control measures are important to minimize the impact of building demolition.